Dampak Covid 19 Terhadap Pendidikan Di SMP Negeri 2 Bahorok Desa Timbang Lawan - Dea Sri Awalina; Kahar Mashuri; Harry Pratama Figna (Prodi Pendidikan IPS STKIP AL MAKSUM, 2022)
Indonesia is one of the countries infected with the Covid-19 pandemic. Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled